7‐3: High ESD Robustness and Low Visible Light Reflectance Design for LTPS‐TFTs on Glass Substrates in Modular Micro‐LED Displays. Issue 1 (25th September 2020) - Son, Seongho; Park, Wonsoon; Lee, Jongsung; Seung, Wanchul; Lee, Changjoon; Seol, Byongsu; Park, Taesang; Chun, Jung-Hoon
Abstract : Low‐temperature poly‐silicon thin‐film transistors (LTPS‐TFTs) on glass substrates in modular micro‐LED displays have metal electrodes which are externally exposed to connect LED chips and pads. This structure increases the risk of electrostatic discharge (ESD) from the external environment. Furthermore, glass substrates cause high visible light reflectance. To improve the ESD robustness and reduce visible light reflectance, a backplane structure with a black fine metal mesh is proposed. Modular micro‐LED displays with the proposed structure achieved the ESD tolerance higher than 8kV through the standard system‐level ESD test and reduced the average visible light reflectance by more than 80%.